Analisis Strategi Pemasaran Konten Kampoeng Radjoet - Michelle Santi Kurniawan; Daniel Hermawan (Pusat P2M Politeknik Negeri Batam, 2022)
Fashion is one of the characteristics of a person showing his lifestyle (life style), especially for women who are more concerned with appearance than men. The fashion trend that is back in popularity in 2020 is the knitted fashion trend, where the age range who likes knitting fashion starts from teenagers to the elderly. The impact of the Covid-19 pandemic has made knitted fashion trends have an effect on sales of Kampoeng Radjoet products because it is seen based on product innovations launched by Kampoeng Radjoet using the concept of handmade manufacture, as well as quality materials so that this knitted product becomes a positive value among the public. society, especially among young people who no longer view knitting as clothing for the elderly or the elderly, but make this knitting a fashion that has high value and is beautiful to look at. In addition, the existence of less intense competition has made Kampoeng Radjoet products a unique product so that sales during the Covid-19 period have increased compared to before. This research aims to analyze the content marketing strategy of Kampoeng Radjoet that has been carried out and its effect on the level of sales. The research method used is qualitative research methods. The data collection technique used is using 4 kinds of data collection techniques, namely observation, interviews, documentation, and triangulation/combination. The triangulation/combined technique used consists of 3 techniques, namely, participatory observation, in-depth interviews, and documentation. The results of the study show that the content marketing strategy carried out by Kampoeng Radjoet has had an influence on sales, but there are still many shortcomings that need to be corrected, especially in the content marketing on social media that it uses.